Estructura territorial y relaciones funcionales en el Corredor del Henares: una aproximación desde la movilidad diaria de la población - Díaz Muñoz, M.a Ángeles; Jiménez Gigante, Francisco José; Lorente Álvarez, Isabel (Anales de Geografía de la Universidad Complutense, 2002)
«Territorial structure and functional relations in the Henares Corridor: an approach from the daily population mobility». This article attempts to study the recent evolution of the population daily mobility with the goal of identifying the possible changes in the dependence relations of Henares Corridor with regard to the capital of Madrid, as well as recognizing the possible configuration of a functional sub-region between the municipalities. We began with the hypothesis that the recent organization of residential and productive spaces —specially manifesting in the outskirt of the metropolitan area of Madrid— has affected such relations. For this study we part from the information provided by the Domiciliary Mobility Surveys done by the Regional Transport Consortium of Madrid in 1988 and 1996.
Keywords: Functional relations; Population daily mobility; Henares Corridor; Region of Madrid